Histiocytosis X; follow-up of 43 cases. Issue 6 (June 1977) - Sims, D G
Abstract : Over a 29-year period, 43 cases of histiocytosis X presented in children under the age of 12 years. 29 patients (67%) have survived, and of these, 15 (52%) have a detectable disability. It was confirmed that young age at presentation and evidence of soft tissue involvement were associated with a worse prognosis. The majority of deaths were associated with pulmonary involvement. 14 patients developed diabetes insipidus. 5 of the surviving adults have heights below the 3rd centile. Puberty usually occurred at a normal age. Follow-up studies on 12 survivors showed no evidence of residual abnormality of haematology, deficient lymphocyte function, or yeast opsonization. HLA typing showed no unusual pattern. Mild carbon monoxide diffusion deffects were present in 4 patients and other abnormalities were detected on lung function tests.